Estructuras y leyes de los hechos causales : primera parte - Guzmán Vicente Burgoa, Lorenzo de ca. 21. Jh. (Sapientia, 2015)
The facts of causality have a dynamic ontological structure, which is as governed by multiple laws or constants; these laws or constants function as regulative «principles» of such causal facts in the various forms it appears in the real world. We say «law» in the sense of conditions or constant demands, which we see or notice on causal facts. And we call them «laws» to distinguish the so-called «principle of causality», which is not a regulator of causal facts, but of our knowledge of such facts. Therefore they have its base in the same empirical observation of causal events and subsequent ontological and scientific reflection. We leave aside, for now, the famous «principle of causality», which regulates rather our knowledge of causation, not the causal facts themselves.